Boilerplate clauses, international commercial contracts and the applicable law - Cordero-Moss, Giuditta (Cambridge : Cambridge University Press, 2011)
'With the aim of creating an autonomous regime for the interpretation and application of the contract, boilerplate clauses are often inserted into international commercial contracts without negotiations or regard for their legal effects. The assumption that a sufficiently detailed and clear language will ensure that the legal effects of the contract will only be based on the contract, as opposed to the applicable law, was originally encouraged by English courts, and today most international contracts have these clauses, irrespective of the governing law. This collection of essays demonstrates that this assumption is not fully applicable under systems of civil law, because these systems are based on principles, such as good faith and loyalty, which contradict this approach'--
'This book addresses the question of whether the drafting style of international contracts may actually achieve rendering the contract self-sufficient. The drafting style, including the recurrence of boilerplate clauses in all types of contracts and irrespective of the governing law, seems to aim at detaching the contract from any elements external to the contract itself, including the applicable law. This drafting style is originally based on the common law approach to contracts, but is now adopted in most international contracts even when they are not subject to a law belonging to the common law family.The analysis follows three different stages, each dealt with in a different part of the book'--
Negotiating international contracts : does the process invite a review of standard contracts from the point of view of national legal requirements? / David Echenberg -- Multinational companies and national contracts / Maria Celeste Vettese -- Does the use of common law contract models give rise to a tacit choice of law or to a harmonised, transnational interpretation? / Giuditta Cordero-Moss -- Common law based contracts under German law / Gerhard Dannemann -- Comparing exculpatory clauses under Anglo-American law : testing total legal convergence / Edward T. Canuel -- Circulation of common law contract models in Europe : the impact of European Union system / Jean-Sylvestre Berge -- The common law tradition : application of boilerplate clauses under English law / Edwin Peel -- The Germanic tradition : application of boilerplate clauses under German law / Ulrich Magnus -- The Romanistic tradition : application of boilerplate clauses under French law / Xavier Lagarde, David Meheut and Jean-Michel Reversac -- The Romanistic tradition : application of boilerplate clauses under Italian law / Giorgio De Nova -- The Nordic tradition : application of boilerplate clauses under Danish law / Peter Mgelvang-Hansen -- The Nordic tradition : application of boilerplate clauses under Finnish Law / Gustaf Moller -- The Nordic tradition : application of boilerplate clauses under Norwegian law / Viggo Hagstrm -- The Nordic tradition : application of boilerplate clauses under Swedish law / Lars Gorton -- The East European tradition : application of boilerplate clauses under Hungarian law / Attila Menyhard -- The East European tradition : application of boilerplate clauses under Russian law / Ivan S. Zykin. --
Includes bibliographical references (p. 374-387) and index.
Keywords: Standardized terms of contract; Contracts -- Language; Foreign trade regulation